2019
DOI: 10.1021/acsami.9b07997
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Nitride: A Bioceramic with a Gift

Abstract: In the closing decades of the 20th century, silicon nitride (Si 3 N 4 ) was extensively developed for high-temperature gas turbine applications. Technologists attempted to take advantage of its superior thermal and mechanical properties to improve engine reliability and fuel economy. Yet, this promise was never realized in spite of the worldwide research, which was conducted at that time. Notwithstanding this disappointment, its use in medical applications in the early 21st century has been an unexpected gift.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 127 publications
4
89
0
Order By: Relevance
“…Eleven Raman bands were located in the monitored spectral window, the precise frequencies of which as well as their physical origins have been reported in a previous paper [10]. In the case of cells cultured on Si 3 N 4 substrates, no significant variations in relative intensity when compared with the positive control sample could be observed after 48 h for RNA/DNA-related Bands 5 (at 783 cm −1 ), 6 (at 794 cm −1 ), and 7 (at 813 cm −1 ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Eleven Raman bands were located in the monitored spectral window, the precise frequencies of which as well as their physical origins have been reported in a previous paper [10]. In the case of cells cultured on Si 3 N 4 substrates, no significant variations in relative intensity when compared with the positive control sample could be observed after 48 h for RNA/DNA-related Bands 5 (at 783 cm −1 ), 6 (at 794 cm −1 ), and 7 (at 813 cm −1 ).…”
Section: Resultsmentioning
confidence: 98%
“…After an initial proposal of osteoinductivity for calcium phosphate containing biomaterials [4,5], only one study has proposed osteoinductivity for alumina ceramics [6]; however, several studies have favored titanium as an osteoinductive substrate [7,8]. Recent in vivo and in vitro studies [9,10] have indicated that silicon nitride, a non-oxide bioceramic previously considered to be fully bioinert [1], is instead a formidable stimulator of osteoblastogenesis and osteoinductivity. The mechanisms of osteoinduction by the above biomaterials have been phenomenologically covered by the above publications, but the fundamental chemistry driving osteoblastogenesis and the successive bone formation needs additional elucidation.…”
Section: Introductionmentioning
confidence: 99%
“…It possesses a unique surface biochemistry that inhibits bacterial infections by longterm elution of nitrogen (promptly converted into ammonia) in minute concentrations that, unlike bacteria and viruses, mammalian cells can easily metabolize. 4 Within 1 minute, influenza A and enterovirus were completely inactivated by Si 3 N 4 bioceramic particles suspended in water. 5 In this study, we exposed SARS-CoV-2 virions to the above bioceramic as well as to aluminum nitride (AlN) micrometric powders suspended in water.…”
Section: Instantaneous "Catch-and-kill" Inactivation Of Sars-cov-2 Bymentioning
confidence: 99%
“…A curious finding is that Si3N4 implants have a lower incidence of bacterial infection (i.e., less than 0.006%) when compared to other implant materials (2.7% to 18%) [14]. This property reflects the complex surface biochemistry of Si3N4 that elutes minute amounts of nitrogen, which is converted to ammonia, ammonium, and other reactive nitrogen species (RNS) that inhibit bacteria [15]. A recent investigation also found that viral exposure to sintered Si3N4 powders in aqueous suspension inactivated H1N1 (Influenza A/Puerto Rico/8/1934), Feline calicivirus, and Enterovirus (EV-A71) [16].…”
Section: Introductionmentioning
confidence: 99%